2018
DOI: 10.1016/j.jmb.2018.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Immunity Protein Recognition of a Type VII Secretion System Exported Antibacterial Toxin

Abstract: Gram-positive bacteria deploy the type VII secretion system (T7SS) to facilitate interactions between eukaryotic and prokaryotic cells. In recent work, we identified the TelC protein from Streptococcus intermedius as a T7SS-exported lipid II phosphatase that mediates interbacterial competition. TelC exerts toxicity in the inner wall zone of Gram-positive bacteria; however, intercellular intoxication of sister cells does not occur because they express the TipC immunity protein. In the present study, we sought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 50 publications
3
54
1
Order By: Relevance
“…We found that at a dose of 8 × 10 7 – 2 × 10 8 of strain RN6390, the mice were asymptomatic and had almost completely cleared the bacteria from lung tissue after 48 hours, whereas a dose of 8 × 10 8 – 2 × 10 9 was lethal to all mice within 12 hours. At a dose of 3 × 10 8 , the mice developed symptoms which resolved within 12 hours, and therefore using this dosage we sought to test whether there was a difference in bacterial proliferation and dissemination dependent on the T7SS. However, after 24 hours of infection with 3 × 10 8 cfu of RN6390 or a cognate Δ essC strain, counts recovered from the lungs and livers of mice infected with the Δ essC strain were not significantly different than those from mice infected with the wild type (Fig S4).…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…We found that at a dose of 8 × 10 7 – 2 × 10 8 of strain RN6390, the mice were asymptomatic and had almost completely cleared the bacteria from lung tissue after 48 hours, whereas a dose of 8 × 10 8 – 2 × 10 9 was lethal to all mice within 12 hours. At a dose of 3 × 10 8 , the mice developed symptoms which resolved within 12 hours, and therefore using this dosage we sought to test whether there was a difference in bacterial proliferation and dissemination dependent on the T7SS. However, after 24 hours of infection with 3 × 10 8 cfu of RN6390 or a cognate Δ essC strain, counts recovered from the lungs and livers of mice infected with the Δ essC strain were not significantly different than those from mice infected with the wild type (Fig S4).…”
Section: Resultsmentioning
confidence: 84%
“…To probe whether TspA is important for S. aureus virulence, we initially developed an immunocompetent murine model of S. aureus pneumonia. Previous reports have indicated that 2-4 × 10 8 colony forming units (cfu) of strain Newman was a suitable infectious dose, and that bacterial proliferation in lung tissue could be observed after 24 hours 38 . We found that at a dose of 8 × 10 7 – 2 × 10 8 of strain RN6390, the mice were asymptomatic and had almost completely cleared the bacteria from lung tissue after 48 hours, whereas a dose of 8 × 10 8 – 2 × 10 9 was lethal to all mice within 12 hours.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations